BASIC MODELS OF INTERACTION BETWEEN THE STATE AND THE PRIVATE SECTOR IN HEALTHCARE - Krylova, Iryna; Palahusynets, Rostyslav (Public Management and Policy, 2025)
The article highlights the unique characteristics of public-private partnerships in healthcare as a means of modernizing medical infrastructure under conditions of limited budgetary financing. It has been established that public-private partnership mechanisms ensure flexible management, resource optimization, and improved quality of medical services. It has been found that project management, logistics, and technology implementation are the main areas of effective partnership. It is emphasized that, in comparison with budget models, public-private partnerships form an institutional system with a clear division of roles. The need for legal, organizational, and managerial tools to support such interaction is emphasized. The importance of policy coordination in the healthcare sector for the stability and predictability of partnerships is noted. It was determined that modeling cross-sectoral links is critical for adequate risk sharing. The content of individual forms of public-private partnerships, particularly concessions, leasing, and renting, was revealed, taking into account the specific needs of medical infrastructure. It was established that there is a need to distinguish between horizontal and vertical links between the private sector and public authorities. The role of patient organizations, communities, and professional communities in the implementation of partnership projects was clarified. It was emphasized that the level of private partner involvement depends on the type of project and the scope of functions transferred. It was emphasized that in infrastructure projects, the private sector is mostly responsible for technical aspects. It was noted that integrated models of public-private partnerships require a higher level of private partner involvement in strategic management. It was determined that the effectiveness of such models is determined by the introduction of quality control mechanisms. The problem of insufficient professional training of personnel for new management practices is revealed. It is established that the transformation to performance management requires institutional adaptation. The need for interdepartmental coordination in planning and financing the industry is emphasized. It is emphasized that Ukrainian legislation creates a flexible basis for mixed contractual forms. It is stated that contracts may simultaneously contain elements of several legal constructs. The risks associated with concluding contracts outside the established procedure for public-private partnerships are identified. It was noted that such practice reduces the level of legal certainty and investment attractiveness. The need for a legal audit of already implemented projects in the medical field was revealed. It was established that mixed contracts in the field of construction of medical facilities require legal and managerial refinement.